ARCHITECTURE TOOLS MEASURE THE LEVELS OF SALT AND PH OF SEAWATER USING A FUZZY LOGIC-BASED ANDROID - Achmad Ubaidillah; Diana Rahmawati; Rocky Aiman (Merdeka Malang University, 2018)
The sea has many potentials to be utilized based on the ecological aspects of coastal area. Almost in the coastal areas and islands in Madura are experiencing difficulties in utilizing marine resources. Salinity changes influenced by water osmotic pressure whereas biota living in salt water should be able to adjust the osmotic pressure from its environment. The changes in pH have an effect on the survival of marine organisms as not all saltwater creatures survive with the change of it. From these problems a system of